Therapeutic Effects of Azithromycin on Spinal Cord Injury in Male Wistar Rats: A Role for Inflammatory Pathways - Rismanbaf, Ali; Afshari, Khashayar; Ghasemi, Mehdi; Badripour, Abolfazl; Haj-Mirzaian, Arvin; Dehpour, Ahmad Reza; Shafaroodi, Hamed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Inflammatory responses, including macrophages/microglia imbalance, are associated with spinal cord injury (SCI) complications. Accumulating evidence also suggests an anti-inflammatory property of azithromycin (AZM).Material and Methods Male Wistar rats were subjected to T9 vertebra laminectomy. SCI was induced by spinal cord compression at this level with an aneurysmal clip for 60 seconds. They were divided into three groups: the sham-operated group and two SCI treatment (normal saline as a vehicle control vs. AZM at 180 mg/kg/d intraperitoneally for 3 days postsurgery; first dose: 30 minutes after surgery) groups. Locomotor scaling and behavioral tests for neuropathic pain were evaluated and compared through a 28-day period. At the end of the study, tissue samples were taken to assess neuroinflammatory changes and neural demyelination using ELISA and histopathologic examinations, respectively. In addition, the proportion of M1/M2 macrophage polarization was assessed by using flow cytometry.Results Post-SCI AZM treatment (180 mg/kg/d for 3 days) significantly improved locomotion (p < 0.01) and decreased sensitivity to mechanical (p < 0.01) and thermal allodynia (p < 0.001). Moreover, there was a significant tumor necrosis factor-α (TNF-α) decline (p < 0.01) and interleukin-10 (IL-10) elevation (p < 0.01) in the spinal cord tissue of the AZM-treated group compared with the control groups 28 days post-SCI. AZM significantly improved neuroinflammation as evidenced by reduction of the M1 expression, elevation of M2 macrophages, and reduction of the M1/M2 ratio in both the dorsal root ganglion and the spinal cord tissue after SCI compared with controls (p < 0.01).Conclusion AZM treatment can be considered a therapeutic agent for SCI, as it could reduce neuroinflammation and SCI sensory/locomotor complications.
Keywords: azithromycin; spinal cord injury; neuropathy; neuroinflammation; rats